Green synthesis and characterization of silver nanoparticles through the Piper cubeba ethanolic extract and their enzyme inhibitory activities - Ahmad, Khalil; Asif, Hafiz Muhammad; Afzal, Taimoor; Khan, Mohsin Abbas; Younus, Muhammad; Khurshid, Umair; Safdar, Maryem; Saifulah, Sohaib; Ahmad, Bashir; Sufyan, Abubakar; Ansari, Siddique Akber; Alkahtani, Hamad M.; et al. (Frontiers in Chemistry, 2023)
The area of 'Green Synthesis of Nano-medicine' as compared to synthetic counterparts is relatively a safer research technology for various biomedical applications, including identification, therapeutic application, and prevention of pathological conditions, pain control, safety and development of human wellness. The present study explored the synthesis and characterization of AgNPs using ethanolic extract of Piper cubeba fruit as a reducing and stabilizing agent, and its potential as an enzyme inhibitory agent. Urease inhibitors are helpful against many severe diseases, including gastric ulcers induced by Helicobacter pylori. The fruits of Piper cubeba plant were taken and ground to fine powder. Plant material was added into 500 ml ethanol and the mixture was filtered. The solvent of filtrate was evaporated, and a thick gummy extract was obtained and stored at 4o C in the refrigerator. AgNPs were green synthesized from solutions of AgNO3 using Piper cubeba extract, which was indicated by a change in the color from light brown to deep brown. The synthesized AgNps were characterized via UV–Vis spectroscopy (UV–Vis), Fourier transform-infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM). Analysis showed the reduction of Ag+ to Ag0 at room temperature (25 °C) and the average particle size of AgNPs was in the range of 40-80 nm. Consequently, the synthesized AgNPs were evaluated for their anti-urease activity. The maximum urease inhibition of Piper cubeba ethanolic extract was 88.5 % at 5 mg conc. and of derived nanoparticles 78.6 % at 0.05 mg conc.. The results were nearly similar to the control drug i.e., Thiourea (0.5 mM & 0.6 mM conc respectively). The study concluded that Piper cubeba extract as well as its green derived AgNps might prove to be a better and safer substitute for their enzyme inhibitory potential in emerging medicine and novel drug delivery techniques to improve and maintain human health.